FUZZY ANALITIC NETWORK PROCESS BASED MULTI CRITERIA DECISION MAKING METHODOLOGY FOR A FAMILY AUTOMOBILE PURCHASING DECISION - (:unkn) unknown (SOUTHERN AFRICAN INST INDUSTRIAL ENGINEERING, 2013)
Nowadays, in parallel with the advancing technology, automobiles that have substantially advanced technological properties are being manufactured. Intended uses of the automobiles have been changing in our days in contrast to 1960s when automobiles were only used for transportation. Consumers, in our day and age, expect profoundly different properties from an automobile. In this context, more than one criterion become effective on making decision on purchasing an automobile that has the required properties. In such a kind of decision problem, making use of Multi Criteria Decision Making (MCDM) methods will ease the solution of the problem and will enable the decision makers to make right decisions. In this study, fuzzy Analytic Network Process (ANP) method, one of the MCDM methods, is used in automobile purchasing decision making. After determining decision criteria and alternatives, network structure of the automobile selection decision problem is formed, and by using fuzzy ANP method, the best one is selected among three alternative automobiles that are in the same segment and are very approximate to each other in terms of their properties and prices.
Keywords: SUPPLIER SELECTION; MODEL; TOPSIS; AHP